Pembinaan Adab Berbasis Peneladanan bagi Anak Migran: Studi Kasus pada Siswa PKBM PNF KBRI Kuala Lumpur - Muhammad Zidan Irfani; Qurroti A’yun (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This research aims to describe the process and results of character education for 4th-grade students at PKBM PNF KBRI Kuala Lumpur thru an educational and habit-based approach. Using a case study design. The research results indicate progressive behavioral development in most students, particularly in greeting and showing respect, bowing when passing teachers, sitting neatly, and walking politely. The changes were not uniform, but the majority of students showed consistent improvement from the first to the third week. Daily guidance in routine forums has proven effective because it optimizes the teacher's role as a moral figure, emotional support, and strengthener of the microsystem environment within the updated Bronfenbrenner bioecological framework, where direct interaction, relationship dynamics, and the influence of technology that accompanies daily life become an integral part of the developmental process. This research confirms that structured, repetitive, and example-based character development can help migrant children build moral and social stability.